Novel piezoelectric thick film actuators - Haigh, Richard (Cranfield University, 2005)
Planar-spiral piezoelectric-unimorph-actuators, that deflect out-of-their-plane, were modelled, designed and fabricated. A range of other planar piezoelectric-device designs has also been made. These include spokes, multi-arms, plates and swastikas. All these devices consisted of a mechanical support in the plane with a piezoelectric layer deposited on top. Impedance spectra demonstrated that a fabricated device was piezoelectrically active. Finite-element (FE) models of straight and spiral piezoelectric- unimorph-actuators were constructed. The mechanical stiffness of the spiral-beam was increased with the curvature of the beam; consequently, the inner coils exhibited virtually no deflection and appeared to be redundant. The advantage of the spiral-actuators is that they allow large actuator lengths to be contained compactly without the loss of mechanical stiffness. Fabrication of the above devices necessitated the development of new fabrication technologies. The active-piezoelectric and mechanical-support were a lead zirconate titanate (Pb(Tii_XZrx)O3 - PZT) thick-film and a-platinised-silicon-wafer respectively. Vias were opened in the PZT with wet etching, and this was completed without damaging the back electrode. Powder blasting allowed any 2-dimensional-shape to be cut into the device wafer. Devices were released from the Si support with deep-reactive-ion-etching (DRIE). The PZT thick films were fired with a Cu20-PbO eutectic additive. Pb and Cu were considered to dope on A and B lattice sites (of PZT) respectively, when the PZT was sintered at high oxygen-partial-pressure (p02). The electrical conductivity of PZT thick films was increased when they were sintered at low P02, and this was moderated by the presence of Cu' as an acceptor ion. A lead-platinum intermetallic and lead silicate glass phase simultaneously formed under sintering conditions of low pot, and this simultaneous formation, was accounted for by a six-stage mechanism. Step 1, residual C in the thick film reduces PbO to Pb followed by step 2 where Pb diffuses into the Pt back electrode. In step 3, Pt3Pb formation occurs in the intermetallic layer followed by step 4 in which PtPb forms. Step 5 occurs with saturation of the intermetallic layer as Pb continues to diffuse from the thick film. There is additional diffusion of Pb into the underlying Si substrate. Finally step 6 occurs at some later point, when P02 has risen, Pb is oxidised to PbO, and Si is oxidised to Si02. PbO and Si02 can flux to form PbSiO3 The glass was found to undermine film/substrate adhesion.